Infrastructure Investments under Uncertainty with the Possibility of Retrofit : Theory and Simulations - Strand, Jon; Miller, Sebastian; Siddiqui, Sauleh (2012)
Investments in large, long-lived, energy-intensive infrastructure investments using fossil fuels increase longer-term energy use and greenhouse gas emissions, unless the plant is shut down early or undergoes costly retrofit later. These investments will depend on expectations of retrofit costs and future energy costs, including energy cost increases from tighter controls on carbon emissions. Simulation analysis shows that the retrofit option can significantly reduce anticipated future energy consumption as of the time of initial investment, and total future energy plus retrofit costs. The more uncertain are the costs, the greater the value of this option. However, the future retrofit option also induces more energy-intensive infrastructure choices, partly offsetting the direct effect of having the option on anticipated energy use. Efficient, forward-looking infrastructure investments have high potential for reducing long-term energy consumption. Particularly if energy prices are expected to rise, however, the potential for reduced energy consumption will be eroded if expectations of energy prices do not include environmental costs or future retrofit possibilities and technologies are not adequately developed.